Providing care under extreme adversity: The impact of the Yemen conflict on the personal and professional lives of health workers. (March 2021) - Elnakib, Shatha; Elaraby, Sarah; Othman, Fouad; BaSaleem, Huda; Abdulghani AlShawafi, Nagiba A.; Saleh Al-Gawfi, Iman Ahmed; Shafique, Fouzia; Al-Kubati, Eman; Rafique, Nuzhat; Tappis, Hannah
Abstract: The war in Yemen, described as the world's 'worst humanitarian crisis, ' has seen numerous attacks against health care. While global attention to attacks on health workers has increased significantly over the past decade, gaps in research on the lived experiences of frontline staff persist. This study draws on perspectives of frontline health workers in Yemen to understand the impact of the ongoing conflict on their personal and professional lives. Forty-three facility-based health worker interviews, and 6 focus group discussions with community-based health workers and midwives were conducted in Sana'a, Aden and Taiz governorates at the peak of the Yemen conflict. Data were analysed using content analysis methods. Findings highlight the extent and range of violence confronting health workers in Yemen as well as the coping strategies they use to attenuate the impact of acute and chronic stressors resulting from conflict. We find that the complex security situation – characterized by multiple parties to the conflict, politicization of humanitarian aid and constraints in humanitarian access – was coupled with everyday stressors that prevented health workers from carrying out their work. Participants reported sporadic attacks by armed civilians, tensions with patients, and harassment at checkpoints. Working conditions were dire, and participants reported chronic suspension of salaries as well as serious shortages of essential supplies and medicines. Themes specific to coping centered around fatalism and religious motivation, resourcefulness and innovation, and sense of duty and patriotism. Our findings demonstrate that health workers experience substantial stress and face various pressures while delivering lifesaving services in Yemen. While they exhibit considerable resilience and coping, they have needs that remain largely unaddressed. Accordingly, the humanitarian community should direct more attention to responding to the mental health and psychosocial needs of health workers, while actively working to ameliorate the conditions in which they work. Highlights: Yemen's healthworkers bear double burden, providing care amid violence and adversity. Healthworkers report disempowerment, distress, fear, anxiety, and burnout. Health workers use problem-focused and meaning-focused coping strategies. Healthworkers serving in conflict-affected areas need increased attention and support.